RELIGIUSITY DIMENSION AND THE EFFECT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ISLAMIC PERSPECTIVE IN AL HUDA KEBUMEN - Siti Nur Azizah (International Conference of Management Science, 2016)
Siti Nur Azizah,Lecturer of STIE Putra Bangsa Kebumen, Doctoral of Management Science Student of Unsoed : 2016. Religious activities are closely related to religiosity, not only occur when performing rituals(worship), but also other activities. Thus, religiosity could predict a person's behavior atwork. Willingness to undertake voluntary workshows that people want to do things that they're no this responsibility. Known as organizational citizenship behavior (OCB) will be very beneficial to the organization. In order to achieve Al Huda as Most Wonderfull Islamic Insitution in Kebumen Distric, the support of teacher as is very important. All members of the organization are in demand to deliver the best performance of the willingness of the people in the organization to contribute positively,more than their formal obligations (OCB). This study aims to analyze the influence of organizational citizenship dimensions of religiosity on behavior islamic prespective (OCBIP) and analyze the dimensions of religiosity influence on organizational citizenship behavior islamic perspective (OCBIP) as well as knowing the conditions and OCB Religiuistasis in Al Huda. To determine the effect of the variables the study used multiple linear regression analysis, whereas to determine the effect of the independent variable on the dependent variable used the elasticity test. To determine the condition of religiosity and OCPP in Al Huda used a quantitative descriptive analysis. The results of statistically using simple regression analysis showed that there was a positive influence of intellectual religiosity toward Organizational Behavior Citizenship Islamic Perspective (OCB IP) but not significant for ritual, ideology, qonsequent and experience religosity. Reviews these results indicate that religiosity intellectual Contributed to increasing of Islamic Perspective Organizational Citizenship Behavior (OCB) Moeslem Among teachers at Al Huda Kebumen